¡Hola Papi! : how to come out in a Walmart parking lot and other life lessons - Brammer, John Paul, 1991- (Simon & Schuster, 2021)
The popular LGBTQ advice columnist and writer presents a memoir-in-essays chronicling his journey growing up as a queer, mixed-race kid in America's heartland to becoming the "Chicano Carrie Bradshaw" of his generation.